THE IMPORTANCE OF CHILDREN'S PROGRAMS ON IRAQI TV AND THEIR EDUCATIONAL IMPACT - Abass, Hussein Ameer; Ahmed, Ahmed Kareem (PT. Antis International Publisher, 2026)
Objective: The purpose of this study is to explore how children’s shows are categorized on Iraqi television and to find out what they might do about social skills for children as well as awareness, logic, and creative thinking. Method: Our research was conducted using a quantitative methodology: questionnaires were given out to children, parents, and teachers in ODK (Open Data Kit) format, while the Smart Plus program was used for data analysis and hypotheses testing. Result: The first hypothesis showed that these programs help children develop various social skills such as cooperation, the courage to explore their world, and love for each other through fun, pedagogical ways. The second hypothesis confirmed that these programs build awareness and logic into young children by providing educational content that supports problem-solving and decision-making. The third hypothesis suggested that through creative narrative, interactive exercises, and puzzles designed to stimulate the brain, children’s shows encourage imaginative thinking. Novelty: The research concludes that children’s television programs, if integrated into a broader system of education involving interaction and practical engagement, can significantly foster holistic child development, highlighting the need for more interactive formats where parents, teachers, and students critically and creatively use the information rather than passively receiving it.